Tandem catalysis with double-shelled hollow spheres - Xiao, Jiadong; Cheng, Kang; Xie, Xiaobin; Wang, Mengheng; Xing, Shiyou; Liu, Yuanshuai; Hartman, Thomas; Fu, Donglong; Bossers, Koen; van Huis, Marijn A.; van Blaaderen, Alfons; Wang, Ye; et al. (Nature materials, 2022)
Metal–zeolite composites with metal (oxide) and acid sites are promising catalysts for integrating multiple reactions in tandem to produce a wide variety of wanted products without separating or purifying the intermediates. However, the conventional design of such materials often leads to uncontrolled and non-ideal spatial distributions of the metal inside/on the zeolites, limiting their catalytic performance. Here we demonstrate a simple strategy for synthesizing double-shelled, contiguous metal oxide@zeolite hollow spheres (denoted as MO@ZEO DSHSs) with controllable structural parameters and chemical compositions. This involves the self-assembly of zeolite nanocrystals onto the surface of metal ion-containing carbon spheres followed by calcination and zeolite growth steps. The step-by-step formation mechanism of the material is revealed using mainly in situ Raman spectroscopy and X-ray diffraction and ex situ electron microscopy. We demonstrate that it is due to this structure that an Fe 2 O 3 @H-ZSM-5 DSHSs-showcase catalyst exhibits superior performance compared with various conventionally structured Fe 2 O 3 -H-ZSM-5 catalysts in gasoline production by the Fischer–Tropsch synthesis. This work is expected to advance the rational synthesis and research of hierarchically hollow, core–shell, multifunctional catalyst materials. Metal oxide–zeolite bifunctional catalysts allow coupling of reactions and so enhance catalytic processes, but structure and reactivity control is difficult. Here, a general synthesis is presented for metal oxide–zeolite double-shelled hollow spheres, which outperform other catalysts for petroleum production.